Analisis Corak Tafsir Adabi Ijtima'i Dalam Tafsir Al-Manar: Studi Atas Pemikiran Muhammad Abduh Dan Rasyid Ridha - Sulfadli; Halimah Basri; Muhammad Irham (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines the adabi ijtima'i (literary-social) style of exegesis as manifested in Tafsir al-Manar, a work born from the intellectual collaboration of Muhammad Abduh and his student, Muhammad Rasyid Ridha, as a response to the decline of the Muslim community in the face of modernity and Western colonialism. The problem addressed is how the adabi style, which emphasizes the linguistic beauty and moral message of the Qur'an, is combined with the ijtima'i style oriented toward solving the social problems of the ummah, and how both figures positioned reason and ijtihad as instruments of exegetical reform. Employing a qualitative library-based method with a historical-analytical approach, this study examines Tafsir al-Manar as a primary source alongside more than thirty recent secondary sources to map the character, strengths, and limitations of this style. The findings show that Tafsir al-Manar presents a tahlili-method tafsir bi al-ra'y that rejects blind imitation, promotes rational ijtihad, and consistently links verse meanings to actual issues such as superstition, oppression, polygamy, and education. This article argues that the adabi ijtima'i style of Abduh and Ridha laid an important foundation for contemporary contextual-thematic exegesis, while leaving a number of methodological critiques that warrant proportional scrutiny.